Empowering Uneducated Workers in Kediri Regency to Increase Employment Opportunities (Jurnal Manajemen Bisnis, 2026)
Uneducated workers are a vulnerable group within the Kediri Regency's labor structure due to limited formal education and low access to decent jobs. This research aims to analyze the conditions of the uneducated workforce and empowerment strategies to increase employment opportunities. The research uses a descriptive qualitative approach through document and literature studies from BPS data, the Department of Manpower, and previous research. The research results show that the number of uneducated workers fluctuated between 2020 and 2024 but remained high. Empowerment strategies include capacity building, community-based economic empowerment, and expanding access to sustainable and locally adaptive regional employment.